Doctors’ Concerns of PDAs in the Ward Round Situation - Alsos, O. A.; Dabelow, B.; Faxvaag, A. (Methods of Information in Medicine, 2011)
Background: Healthcare professionals in hospital care increasingly use small-screen handheld computers. Studies that have investigated doctors’ concerns about handheld usage have mainly focused on technical, organizational and performance issues. Very few have looked at the effects of Personal Digital Assistants (PDAs) on the interaction between physician and patient.Objective: The aim of this study was to explore the effects of PDA usage on the physicians’ prescription work, their concerns about using it in point-of-care situations, and the effects on the patient-physician dialog.Methods: We used a qualitative and comparative approach where 14 physicians each carried out four simulated ward rounds in which they modified the medication of patient actors using a paper-based medical chart and three versions of a PDA-based system. We analyzed ward round video recordings, semi-structured interviews with the doctors, and focus group using approaches based on ethnomethodology and grounded theory.Results: Physicians used PDA and paper differently. Physicians’ actions, as well as their non-verbal communication, were less transparent and clear for the patient when using a PDA. Doctors were worried about distractions from the handheld device and about a negative impact on the physician-patient conversation. In general, physicians were more comfortable with paper, but preferred PDA because it offered an undo function and reduced the need to memorize drug names and dosages by providing concrete alternatives in the user interface.Conclusions: Despite the many benefits, PDA usage at the point-of-care comes with the increased risk of distractions for physicians and can cause a negative patient experience. Designers of point-of-care systems need to be aware of, and address, the problems with handhelds and learn from the attributes and access capabilities of paper charts.
Keywords: Mobile computing; PDA; handheld; distractions; physician-patient communication; point-of-care; bedside computing; usability evaluation